A genomics resource for genetics, physiology, and breeding of West African sorghum. Issue 2 (5th April 2021) - Faye, Jacques M.; Maina, Fanna; Akata, Eyanawa A.; Sine, Bassirou; Diatta, Cyril; Mamadou, Aissata; Marla, Sandeep; Bouchet, Sophie; Teme, Niaba; Rami, Jean‐Francois; Fonceka, Daniel; Cisse, Ndiaga; et al.
Abstract: Local landrace and breeding germplasm is a useful source of genetic diversity for regional and global crop improvement initiatives. Sorghum ( Sorghum bicolor L. Moench) in western Africa (WA) has diversified across a mosaic of cultures and end uses and along steep precipitation and photoperiod gradients. To facilitate germplasm utilization, a West African sorghum association panel (WASAP) of 756 accessions from national breeding programs of Niger, Mali, Senegal, and Togo was assembled and characterized. Genotyping‐by‐sequencing (GBS) was used to generate 159, 101 high‐quality biallelic single nucleotide polymorphisms (SNPs), with 43% in intergenic regions and 13% in genic regions. High genetic diversity was observed within the WASAP (π = .00045), only slightly less than in a global diversity panel (GDP) (π = .00055). Linkage disequilibrium (LD) decayed to background level ( r 2 < .1) by ∼50 kb in the WASAP. Genome‐wide diversity was structured both by botanical type and by populations within botanical type with eight ancestral populations identified. Most populations were distributed across multiple countries, suggesting several potential common gene pools across the national programs. Genome‐wide association studies (GWAS) of days to flowering (DFLo) and plant height (PH) revealed eight and three significant quantitative trait loci (QTL), respectively, with major height QTL at canonical height loci Dw3 and SbHT7.1 . Colocalization of two of eight major flowering time QTL with flowering genes previously described in U.S. germplasm ( Ma6 and SbCN8 ) suggests that photoperiodic flowering in West African sorghum is conditioned by both known and novel genes. This genomic resource provides a foundation for genomics‐enabled breeding of climate‐resilient varieties in WA. Core Ideas: A West African sorghum panel ( n = 756) was assembled from four national programs. Over 150, 000 genome‐wide nucleotide polymorphisms were genotyped by sequencing. Diversity was structured by subpopulation within botanical type and across countries. Known genes and novel loci for flowering time and plant height were identified.